Pengelolaan Clungup Mangrove Conservation (CMC) Tiga Warna oleh Yayasan Bhakti Alam Sendang Biru di Kabupaten Malang, Jawa Timur - Chrissanty, Nadia; Bhaskara, Gde Indra; Nugroho, Saptono (Jurnal Ilmiah Wahana Pendidikan, 2024)
Clungup Mangrove Conservation (CMC) Tiga Warna is an ecotourism destination in Tambakrejo Village, Sumbermanjing Wetan District, Malang Regency. In tourism activities, especially ecotourism, a management system is needed to optimally utilize the potential and maintain the destination's sustainability into the future. The ecotourism management process consists of the planning stage, the implementation stage, and the monitoring and evaluation stage. CMC Tiga Warna is managed directly by the Bhakti Alam Sendang Biru Foundation. The aim of this study is to determine the application of ecotourism management by the management using qualitative-descriptive analysis. The findings of this study found that Yayasan Bhakti Alam Sendang Biru has done ecotourism management quite well, but the foundation has not yet implemented an ecotourism zoning system. The checklist system is their strong point.